THE INFLUENCE OF BRAND AWARENESS, BRAND LOYALTY AND QUALITY ON PURCHASE INTENTION OF REALME SMARTPHONE PRODUCTS IN LHOKSEUMAWE CITY (Case Study in the Community of Lhokseumawe City) - Riski Rahmadani; Muchsin; Julimursyida; Samsul Bahri; Henny Irawati (RADJA PUBLIKA, 2024)
This research aims to determine the influence of Brand Awareness, Brand Loyalty, Perceived Quality on Purchase Intention for Realme Smartphone Products in Lhokseumawe City. The Brand Awareness indicators used in this research consist of being easy to remember, recognizing the type of product, having good quality and affordable prices, and good satisfaction. Then the Brand Loyalty indicators consist of trust, paying more, inviting people to buy, repeat purchases, following the news, and being able to become a spokesperson. Then the Perceived Quality Indicator consists of good quality, consistent quality, reliable products. And the Purchase Intention indicators used consist of transactional, referential and exploratory. This research uses a quantitative type with a sampling technique in the form of Accidental Sampling. The data used in this research is primary data obtained by distributing questionnaires to 102 Lhokseumawe City residents who are interested in buying Realme Smartphone Products. The data analysis technique used in this research is multiple linear regression analysis using SPSS version 23 software. The results of the research show that Brand Awareness, Brand Loyalty have a positive and significant effect on Purchase Intention for Realme Smartphone Products in Lhokseumawe City, while Perceived Quality has no significant effect on Purchase Intention for Realme Smartphone Products in Lhokseumawe City.